1953
DOI: 10.1021/ie50524a019
|View full text |Cite
|
Sign up to set email alerts
|

Flame Stability in Bluff Body Recirculation Zones

Abstract: stabilization of a flame in the eddy region behind a bluff body in a high velocity gas stream is a process of practical as well as theoretical interest. (A bluff body consists of any immersed object whose downstream shape is blunt enough to create a wake of eddies in the stream behind the object.) The practical interest arises because some high output combustorsê .g., for jet engines-anchor the flame in this manner.A flame so stabilized can be made to spread throughout the entire flammable mixture. Flame stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

1972
1972
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(60 citation statements)
references
References 2 publications
2
58
0
Order By: Relevance
“…This lean blowout limit has been found to correspond to a fuel equivalence ratio of about 0.49, very close to the lean flammability limit of the propane fuel and air (ca 0 = 0.50, Lewis and von Elbe, 1987). Other studies (Sturgess, et al 1990;Longwell, et al, 1953) suggest that the combustor is behaving like a well stirred reactor when it Is near its lean blowout limit.…”
Section: Introductionsupporting
confidence: 55%
“…This lean blowout limit has been found to correspond to a fuel equivalence ratio of about 0.49, very close to the lean flammability limit of the propane fuel and air (ca 0 = 0.50, Lewis and von Elbe, 1987). Other studies (Sturgess, et al 1990;Longwell, et al, 1953) suggest that the combustor is behaving like a well stirred reactor when it Is near its lean blowout limit.…”
Section: Introductionsupporting
confidence: 55%
“…Longwell et al [7] suggested that the recirculation zone behind a bluff body could be assumed as a perfect stirred reactor (PSR). The schematic of Longwell's PSR model is shown in Figure 1.…”
Section: Longwell's Psr Modelmentioning
confidence: 99%
“…The primary concern here is the potential for leaked working fluid to become trapped in the recirculation regions aft of the finned tubes. The stabilization of a flame in the eddy region behind a bluff body in a high velocity gas stream is a well known phenomenon used to anchor the flame in the combustors of jet engines [7]. A flame stabilized in this manner can spread throughout the entire flammable mixture.…”
Section: Manufacturing Defectsmentioning
confidence: 99%